Temperature-dependent magnetic damping of yttrium iron garnet spheres - Maier-Flaig, H.; Klingler, S.; Dubs, Carsten; Surzhenko, O.; Gross, Rudolf; Weiler, Mathias; Huebl, Hans; Goennenwein, S. T. B. (Physical Review B, 2017)
We investigate the temperature-dependent microwave absorption spectrum of an yttrium iron garnet sphere as a function of temperature (5 to 300K) and frequency (3 to 43.5GHz). At temperatures above 100K, the magnetic resonance linewidth increases linearly with temperature and shows a Gilbert-like linear frequency dependence. At lower temperatures, the temperature dependence of the resonance linewidth at constant external magnetic fields exhibits a characteristic peak which coincides with a non-Gilbert-like frequency dependence. The complete temperature and frequency evolution of the linewidth can be modeled by the phenomenology of slowly relaxing rare-earth impurities and either the Kasuya-LeCraw mechanism or the scattering with optical magnons. Furthermore, we extract the temperature dependence of the saturation magnetization, the magnetic anisotropy, and the g factor.
CRIS-Team Scopus Importer:2023-03-27